(untitled) (Scientific journal of the Fergana State University, 2023)
In this paper, we have considered a Tricomi type problem for mixed type equation with Hilfer’s double order derivative sub-diffusion equation and classical wave equation in a composite domain. Main methods of the investigation are a method of integral equations and energy integrals’ method